Rancang Bangun Media Pembelajaran Multibahasa Berbasis Web Menggunakan Metode Rapid Application Development - Firdausi Usqi Salsabilah; Uce Indahyanti; Suhendro Busono; Yulian Findawati (LPPM UBHINUS MALANG, 2025)
This study aims to develop a web-based multilingual language learning media using the Rapid Application Development (RAD) method. This system supports learning five languages, namely English, Mandarin, Russian, Arabic, and English, through various features such as material management, quizzes, lectures, language levels, and integration with Telegram groups. RAD is used to accelerate the development process by enabling active participation of users in all departments. This study found that web-based language learning media meets user needs and provides an interactive learning experience, collaboration, and personal learning. This media is also equipped with intuitive navigation and clear visuals. This study makes a significant contribution to the development of multilingual language learning media and is an effective solution to improve the quality of global language learning. The application of the RAD method is efficient and can be applied to system development. For broader development, analytical learning and integration with external platforms can improve system functionality.